Mapping Reflective Thinking Patterns of Prospective Professional Teachers - Yuniawatika; Wibowo, Sigit; Manggala, Ibrahim (Universitas Pendidikan Ganesha, 2025)
Reflective thinking is one of the essential cognitive skills that teachers must possess to enhance the quality of teaching. However, many prospective teachers still struggle to develop deep reflection on their teaching practices. This study aims to analyze the patterns of reflective thinking among pre-service teacher education students, with a focus on cognitive levels C4-C6. This research employs a qualitative approach with an Interpretive Phenomenological Analysis design. The subjects of this study are 36 pre-service teacher education students, who also serve as the experimental subjects. Data collection was carried out through in-depth interviews and documentation of students' reflections using semi-structured interview guidelines and reflection analysis sheets. Data analysis followed the stages of data managing, reading-memoing, describing-classifying-interpreting, and representing-visualizing. The findings reveal four patterns of reflective thinking: habitual action, understanding, reflection, and critical reflection. Each pattern represents different levels of depth in thinking and self-awareness during the learning process. The conclusion of this study indicates that there is variation in the reflective thinking patterns among pre-service teachers, which has implications for their professional development. The implications of this research emphasize the importance of training and fostering reflective thinking to shape character, professional competence, and enhance teaching effectiveness in an ever-evolving educational landscape.